(untitled) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
This paper deals with the investigation of youth language in Jordanian Facebook communities. The analysis covered nearly 500 humorous posts containing the samples of the studied age group’s language creativity online. It was also explicated that the participants of such multilingual and multicultural communities as the social media feel the urge to use specific tools of self-expression and self-identification. For this purpose, a particular language and sociocultural codes are actively utilized. The subject of investigation involves linguistic and sociolinguistic peculiarities of Jordanian youth posts in online communities. This study reveals some graphic transmission peculiarities of the slang in the informal online communication since the colloquial Arabic varieties utilized in the new media are de facto not encrypted in the official register. It is pointed out that the society’s democratic aspirations, the worship of western culture and the lack of strict state control over the online communication contribute to the development of unofficial Arabic varieties on Facebook. The author focuses on the Arabic / English code mixing, the integration of the English slang lexis in the Jordanian online communication, the utilization of language play in the derivation process etc. The present study has shown the high level of openness of the Jordanian youth slang for the borrowing, language and culture contacts, innovative tools for the language change. This phenomenon is caused by the long lasting impact of the English culture on the Jordanian society both in the real world and in the web. On the other hand, it was found that the informal youth communication involving the obscene lexicon and enantiosemy preserves the world tendency to the usage of low level language as a means of self-expression in the social media.